2014
DOI: 10.1177/0363546514548019
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pelvic Incidence With Cam and Pincer Lesions

Abstract: While the study results do not prove a causal relationship, it is theorized that the restriction of range of motion and biomechanical adaptations of the pelvis around the hip joints resulting from a smaller PI may affect hip development and FAI. The influence of mechanical factors beyond the hip joint in the development of FAI should be considered by clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 30 publications
0
61
1
Order By: Relevance
“…Therefore, no predictable, consistent pattern of spur formation can be expected in patients with AAI with associated bony exostoses off the tibia and/or talus. In addition, congenital, bony morphological variants such as squatting talar facets or double tibial facets could in principle predispose to impingement spur formation in the ankle, similar to morphological variants reported for femoroacetabular impingement (Gebhart et al, 2014;Jung et al, 2011;Satinoff, 1972).…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, no predictable, consistent pattern of spur formation can be expected in patients with AAI with associated bony exostoses off the tibia and/or talus. In addition, congenital, bony morphological variants such as squatting talar facets or double tibial facets could in principle predispose to impingement spur formation in the ankle, similar to morphological variants reported for femoroacetabular impingement (Gebhart et al, 2014;Jung et al, 2011;Satinoff, 1972).…”
Section: Discussionmentioning
confidence: 60%
“…Gebhart et al [ 24 ] evaluated 40 cadaveric pelves (80 hips) with photography and manual goniometry and compared PI between hips showing cam- or pincer-related bony abnormalities and hips without those abnormalities. They found that PI was significantly lower in both patterns of FAI compared with controls—43.1° ± 8.6° in 40 cam-FAI hips versus 47.7° ± 9.3° in 40 control hips ( p = 0.02), and 42.5° ± 8.5° in 28 pincer-FAI hips versus 47.0° ± 9.2° in 52 control hips ( p = 0.04).…”
Section: Resultsmentioning
confidence: 99%
“…8 A decreased pelvic incidence has been related to radiographic signs of FAI, as well. [9][10][11][12] These results suggest that limited range of motion in the spine can alter spinopelvic parameters and subsequently change the joint mechanics of the hip. The article published by Chandrasekaran, Darwish, Suarez-Ahedo, Lodhia, and Domb, 13 "Outcomes of Hip Arthroscopy in Patients With Previous Lumbar Spine Surgery: A Matched-Pair Controlled Cohort Study With Minimum Two-Year Follow Up," brings a good topic of discussion suggesting that patients with a history of lumbar spine surgery undergoing hip arthroscopy should expect improvement in symptoms following surgery.…”
Section: See Related Article On Page 443mentioning
confidence: 88%